Reusable design: A proposed approach to Public Health Informatics system design - Revere Debra; Demiris George; Hills Rebecca A; Reeder Blaine; Pina Jamie (BMC, 2011)
Abstract Background Since it was first defined in 1995, Public Health Informatics (PHI) has become a recognized discipline, with a research agenda, defined domain-specific competencies and a specialized corpus of technical knowledge. Information systems form a cornerstone of PHI research and implementation, representing significant progress for the nascent field. However, PHI does not advocate or incorporate standard, domain-appropriate design methods for implementing public health information systems. Reusable design is generalized design advice that can be reused in a range of similar contexts. We propose that PHI create and reuse information design knowledge by taking a systems approach that incorporates design methods from the disciplines of Human-Computer Interaction, Interaction Design and other related disciplines. Discussion Although PHI operates in a domain with unique characteristics, many design problems in public health correspond to classic design problems, suggesting that existing design methods and solution approaches are applicable to the design of public health information systems. Among the numerous methodological frameworks used in other disciplines, we identify scenario-based design and participatory design as two widely-employed methodologies that are appropriate for adoption as PHI standards. We make the case that these methods show promise to create reusable design knowledge in PHI. Summary We propose the formalization of a set of standard design methods within PHI that can be used to pursue a strategy of design knowledge creation and reuse for cost-effective, interoperable public health information systems. We suggest that all public health informaticians should be able to use these design methods and the methods should be incorporated into PHI training.